Responsibility of Local Governments in Fulfilling the Right to Food - Mulyani Zulaeha; Lies Ariany; Rahmat Halim Sapoetra; Nabilla Nurrosyifa Azzahra (Scholar Center, 2023)
Government Regulation Number 17 of 2015 concerning Food Security and Nutrition states that the Provincial Government, Regency/City Government, and/or Village Government implement policies and are responsible for the implementation of food security in their respective regions. Food security must be prioritized, and support from the Local Government and the Central Government in maintaining food security is important to prevent food crises. This study aims to analyze the policy of the Regional Government in managing food needs and providing food reserves so as to provide protection for the fulfillment of the right to food in South Kalimantan. Through socio-juridical research methods (socio-legal) using an interdisciplinary or